\(P=\left(\dfrac{10+2\sqrt{x}}{x-\sqrt{x}-2}+\dfrac{\sqrt{x}+1}{2-\sqrt{x}}\right):\dfrac{\sqrt{x}+3}{\sqrt{x}-2}\)
\(=\left(\dfrac{2\sqrt{x}+10}{\left(\sqrt{x}-2\right)\left(\sqrt{x}+1\right)}-\dfrac{\sqrt{x}+1}{\left(\sqrt{x}-2\right)}\right)\cdot\dfrac{\sqrt{x}-2}{\sqrt[]{x}+3}\)
\(=\dfrac{2\sqrt{x}+10-\left(\sqrt{x}+1\right)^2}{\left(\sqrt{x}-2\right)\left(\sqrt{x}+1\right)}\cdot\dfrac{\left(\sqrt{x}-2\right)}{\sqrt{x}+3}\)
\(=\dfrac{\left(2\sqrt{x}+10-x-2\sqrt{x}-1\right)}{\sqrt{x}+1}\cdot\dfrac{1}{\sqrt{x}+3}\)
\(=\dfrac{9-\sqrt{x}}{\left(\sqrt{x}+1\right)\left(\sqrt{x}+3\right)}=\dfrac{\left(3-\sqrt{x}\right)\left(3+\sqrt{x}\right)}{\left(\sqrt{x}+1\right)\left(\sqrt{x}+3\right)}\)
\(=\dfrac{3-\sqrt{x}}{\sqrt{x}+1}\)